2017
DOI: 10.1155/2017/3259329
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Performance of Urinary Mycobacterium tuberculosis Antigens Cocktail (ESAT6, CFP10, and MPT64) with Culture and Microscopy in Pulmonary Tuberculosis Patients

Abstract: Pulmonary tuberculosis (TB) is a major global health problem and is one of the top 10 causes of death worldwide. Our study aimed to evaluate the performance of urinary Mycobacterium tuberculosis (Mtb) antigens cocktail (ESAT6, CFP10, and MPT64) compared with culture and microscopy. This descriptive cross-sectional study was conducted in Dr. Hasan Sadikin General Hospital, Bandung, from January 2014 to October 2016. A total of 141 pulmonary tuberculosis patients were included. Sputum samples were examined for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…A higher sensitivity of 71% was found in a study involving adult population, using TB antigens cocktail, ESAT-6, CFP-10, and MPT-64 rapid immunochromatography test (21). However, it remained unclear whether it was due to the multiple specific antigens used in the cocktail (compared to a single antigen in our study) or higher concentration of CFP-10 in urinary specimens of adult TB patients, which typically showing more positive results on M.tb culture.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A higher sensitivity of 71% was found in a study involving adult population, using TB antigens cocktail, ESAT-6, CFP-10, and MPT-64 rapid immunochromatography test (21). However, it remained unclear whether it was due to the multiple specific antigens used in the cocktail (compared to a single antigen in our study) or higher concentration of CFP-10 in urinary specimens of adult TB patients, which typically showing more positive results on M.tb culture.…”
Section: Discussionmentioning
confidence: 90%
“…However, due to lower specificity, it was not meant to replace the conventional microscopic examination and M.tb culture. To increase the sensitivity and positive predictive value of urinary CFP-10 level, it should be used in conjunction with microbiological examination (21). A positive result on urinary CFP-10 levels would provide better diagnostic predictive value in both clinically and microbiologically confirmed TB cases than those only microbiologically confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, I-PCR comprises the versatility of ELISA with the enormous amplification capacity of PCR, thereby exhibiting many-fold higher sensitivity than ELISA [17]. Moreover, urine is quite easy to obtain that has a lesser risk of infection to the laboratory workers but it carries low concentration of M. tuberculosis biomarkers [18]. Detection of mycobacterial lipoarabinomannan (LAM) within urine samples is considered as an attractive biomarker, which has been demonstrated in HIV-coinfected and HIVuninfected TB individuals by lateral flow immunochromatography and ELISA methods though poor sensitivities were observed in HIV-uninfected TB individuals [17,19].…”
Section: Immuno-pcrmentioning
confidence: 99%
“…In one study, Turbawaty et al attempted to detect the presence of all the three antigens in urine using a cocktail of polyclonal antibodies against all the three antigens. The authors showed that this strategy increased the sensitivity to 90%, although the specificity remained poor at <30% (Turbawaty et al, 2017).…”
Section: Prospects Of Detecting Miscellaneous Components Of Mtbmentioning
confidence: 99%